2015
DOI: 10.1371/journal.pone.0138099
|View full text |Cite
|
Sign up to set email alerts
|

Serum Homocysteine Concentration Is Significantly Associated with Inflammatory/Immune Factors

Abstract: Recent studies suggest that serum homocysteine (HCY) level is correlated to inflammatory/immune factors that influence the development and progression of many diseases, such as cardiovascular disease. However, the association between serum HCY level and inflammatory/immune factors in healthy populations has not been systematically investigated. This study was conducted based on the Fangchenggang Area Male Health and Examination Survey (FAMHES) project. After comprehensive baseline analysis, we could not find a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 37 publications
0
26
0
Order By: Relevance
“…31 Insulin resistance is also linked to inflammatory cytokine stimulation. 32 Homocysteine was shown to be significantly associated with serum C4, CRP, and IgM level, 51 and DNA hypomethylation of some of genes was also shown to be an important factor in inflammation. 52 So it is possible that hyperhomocysteinemia and/or DNA hypomethylation cause systemic inflammation in MTHFR C677T variants patients, and systemic inflammation becomes a more direct and more relevant pathogenesis for MTHFR C677T polymorphism-related disease.…”
Section: Discussionmentioning
confidence: 99%
“…31 Insulin resistance is also linked to inflammatory cytokine stimulation. 32 Homocysteine was shown to be significantly associated with serum C4, CRP, and IgM level, 51 and DNA hypomethylation of some of genes was also shown to be an important factor in inflammation. 52 So it is possible that hyperhomocysteinemia and/or DNA hypomethylation cause systemic inflammation in MTHFR C677T variants patients, and systemic inflammation becomes a more direct and more relevant pathogenesis for MTHFR C677T polymorphism-related disease.…”
Section: Discussionmentioning
confidence: 99%
“…As described in our previous studies 27 , 28 , the FAMHES project was carried out from September to December 2009, and involved a routine physical examination at the Medical Center in Fangchenggang First People’s Hospital. The sample comprised 4303 non-institutionalized Chinese men aged 17 to 88 years old, who were from the Fangchenggang area of Guangxi, China.…”
Section: Methodsmentioning
confidence: 99%
“…The levels of hs-CRP can reflect the composition of atherosclerotic plaques and predict the possibility of plaque rupture. 36 The studies 37 show that hs-CRP in serum are significantly associated with homocysteine concentration. A previous study 38 showed that hs-CRP was closely related to carotid plaque and IMT.…”
Section: Levels Of Hs-crp In Unstable Carotid Plaque and LImentioning
confidence: 99%